Exploring the psychosocial impact of simple robotic assistive technology on adolescents with neuromuscular disease. (28th March 2022) - Oldford, Laura; Hanson, Natasha; Ross, Isabelle; Croken, Emma; Bleau, Lise
Introduction: Adolescents with neuromuscular disease face significant challenges accessing social leisure activities. Assistive technology has provided new opportunities for those with neuromuscular disease to augment their social lives and leisure pursuits. However, there is limited research evaluating the impact of these technologies. Methods: This study employed mixed methods to evaluate the potential impact of simple robotics on psychosocial factors and quality of life for those adolescents living with neuromuscular diseases. Semi-structured qualitative interviews were performed, as well as the adult Psychosocial Impact of Assistive Technology Device (PIADS) with 9 adolescents, ranging in age from 13 to 19 years old. Results: Thematic analysis of the qualitative data resulted in five major themes: everyday lives and seasonality; socialization; leisure activities; robotics as a leisure activity; and ease of use of robotics. The PIADS found the individual scores demonstrated a range from very little yet positive perceived impact to maximum positive impact in each subscale (competence, adaptability, and self-esteem). Conclusions: Simple mainstream robotics, paired with personalized access methods to control them, offer potential leisure and social integration opportunities to adolescents with neuromuscular diseases in a variety of settings, indoors and outdoors. The findings of this study suggest there are opportunities for this type of mainstream technology to be applied not just to adolescents, but potentially children of all ages with neuromuscular disease, across a variety of environments.